Integral and shell-MIP display algorithms in MR and CT three-dimensional models of the brain surface. - Casey, S O; Rubinstein, D; Lillehei, K O; Alberico, R A; Ozsvath, R R; Cajade-Law, A G; Weprin, B E; Michel, E; Truwit, C L (American Journal of Neuroradiology, 1998)
BACKGROUND AND PURPOSE Our purpose was to demonstrate the use of integral and shell maximum intensity projection (shell-MIP) display algorithms in the 3-D CT and MR depiction of cerebral gyral and surface venous anatomy and disorders. These new algorithms are compared against MIP and shaded-surface-display (SSD) algorithms.METHODS Integral and shell-MIP displays were generated from a specified number of proximal surface voxel layers in a 3-D model. Algorithmic models were compared on nine contrast-enhanced spoiled gradient-recalled acquisition in a steady state (SPGR) MR venograms for brain surface anatomic identification and detail. Seven CT venograms were compared for conspicuity of filling defects. Twelve contrast-enhanced preoperative planning 3-D MR models were rated for neurosurgical utility.RESULTS A shell-MIP score of 7.00 and an integral score of 6.78 represented the highest mean subjective MR gyral quality (1-10 scale) followed by an SSD score of 3.89 and an MIP score of 1.06. Mean confidence scores for MR central sulcus identification (1-10 scale) were shell-MIP, 7.67; integral, 7.00; SSD, 3.22; and MIP, 1.00. Mean superficial venous quality MR ratings (1-10 scale) were shell-MIP, 8.22; MIP, 7.39; integral, 7.00; and SSD, 3.72. The mean number of cortical veins draining into each side of the superior sagittal sinus on MR was as follows: MIP, 6.19; integral, 6.06; shell-MIP, 5.94; and SSD, 3.81. Mean confidence scores for filling defect identification on CT venograms (1-5 scale) revealed a shell-MIP score of 4.36 and an integral score of 4.29 to be superior to a MIP score of 3.00. In selected cases, 3-D presurgical planning, prior to tumor resection, was clinically useful.CONCLUSION Integral and shell-MIP are useful 3-D display algorithms for simultaneous display of superficial cerebral veins and gyri on MR images and of thrombosis on CT venograms.